2022
DOI: 10.1002/ncp.10866
|View full text |Cite
|
Sign up to set email alerts
|

Blenderized enteral nutrition in pediatric short gut syndrome: Tolerance and clinical outcomes

Abstract: Background Blenderized feeds consisting of whole food components are emerging as a preferred approach to enteral nutrition. However, there is limited evidence‐based guidance for this strategy in short bowel syndrome (SBS). We aimed to explore the tolerance and clinical outcome of blenderized feeds in patients with SBS. Method We conducted a single‐center, retrospective study of blenderized feeds in pediatric SBS. Of the 376 patients screened, 58 met inclusion criteria. Three patients were excluded because of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…36,37 Furthermore, existing approaches used in SBS-IF, such as teduglutide or blenderized feeding regimens, may not prevent these deficiencies. [38][39][40] There were no differences in villous height or crypt depth on intestinal morphometric analysis, potentially related to the short study duration (Figs. 4A-D).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…36,37 Furthermore, existing approaches used in SBS-IF, such as teduglutide or blenderized feeding regimens, may not prevent these deficiencies. [38][39][40] There were no differences in villous height or crypt depth on intestinal morphometric analysis, potentially related to the short study duration (Figs. 4A-D).…”
Section: Discussionmentioning
confidence: 98%
“…Regardless, the changes in nutritional markers are important considering that steatorrhea in SBS is linked to micronutrient deficiencies and associated comorbidities such as metabolic bone disease, vision loss, neuropathies, cardiomyopathy, and coagulopathy, among others 36,37 . Furthermore, existing approaches used in SBS-IF, such as teduglutide or blenderized feeding regimens, may not prevent these deficiencies 38–40 …”
Section: Discussionmentioning
confidence: 99%
“…A recent case series described children with unexpected poor growth when switched to CBF due to presumed inaccuracies in formula delivery via feeding pumps 10 . In another retrospective case series of children with short bowel syndrome who transitioned to using blenderized feeds after using more traditional formulas, 11 the majority had improved diarrhea. Despite this, 47% of this group experienced weight loss or poor weight gain when using CBFs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated improvement in gastrointestinal (GI) symptoms when children of various medical backgrounds, including neuromuscular, metabolic, and oropharyngeal disorders, were prescribed BTF 16–18 . In a small cohort ( n = 58) of children with short bowel syndrome, BTFs were associated with an improvement in diarrhea, but patients with a colonic resection struggled with weight maintenance 19 . The Blenderized Enteral Nutrition Study (BLEND) showed improvements in micronutrient provision, vomiting, and stool microbial diversity in a group of 20 hospitalized pediatric patients 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In a small cohort (n = 58) of children with short bowel syndrome, BTFs were associated with an improvement in diarrhea, but patients with a colonic resection struggled with weight maintenance. 19 The Blenderized Enteral Nutrition Study (BLEND) showed improvements in micronutrient provision, vomiting, and stool microbial diversity in a group of 20 hospitalized pediatric patients. 20 Data in adults using BTF are more sparse and limited to small study populations and specific disease states.…”
Section: Introductionmentioning
confidence: 99%